Hidden Struggles in Higher Education: A Systematic Review of Adjustment Experiences of Minority - Alimuddin, Najiba; Alwi, M. Ahkam; Nur, Haerani (Universitas Muhammadiyah Magelang, 2026)
Student adjustment in higher education is a key determinant of academic success, psychological well-being, and study persistence. In the Indonesian context, minority students including those from different cultural, ethnic, religious backgrounds, students with disabilities, and other marginalized groups often face more complex adjustment challenges. This study aims to systematically review the literature on adjustment challenges, coping strategies, and supporting factors influencing minority students’ adaptation in higher education. This study employed a Systematic Literature Review (SLR) approach by analyzing national and international peer reviewed journal articles published between 2015 and 2025. Data were collected through Google Scholar, Scispace, and reputable journal platforms and analyzed using qualitative content analysis. The findings reveal that minority students commonly experience academic pressure, acculturative stress, emotional difficulties, and social exclusion. Effective coping strategies such as emotion-focused coping, problem-focused coping, and social support seeking play an important role in overcoming these challenges. Furthermore, perceived social support, psychological capital, and inclusive institutional environments consistently support successful adjustment. These findings highlight the importance of inclusive policies and comprehensive support systems within Indonesian higher education to promote equitable student success and well being.